Corporate social responsibility and the non-linear effect on audit opinion for energy firms in Vietnam - Xuan Hung Nguyen; Hiep-Thien Trinh (Cogent Business & Management, 2020)
Corporate social responsibility (CSR) has increasingly been researched in the current and future trend of sustainable development. Extant studies document mixed results about the relationship between CSR and earnings management, but very few papers discuss how CSR and audit opinion are related. Using a sample of all the energy firms listed in Vietnam from 2007 to 2017, the research results suggest that CSR-engaged firms are more likely to receive unqualified opinions on the quality of their financial statements. We further document that firms benefit from CSR activities only when the activities are not at high levels, or there exists a non-linear effect of CSR on the likelihood of receiving unqualified opinion. This suggests that firms should balance the costs and benefits of CSR. The study conducts several robustness tests and the results remain unchanged throughout these tests.
Keywords: 650; corporate social responsibility; audit opinion; Vietnam